Remembering John Newsom-Davis' contribution to human imaging in Oxford. - Matthews, P; Radda, G; Johansen-Berg, H; Tracey, I; Cowey, A (2008)
John Newsom-Davis played a crucial role in supporting areas of scientific exploration beyond his own research interests. In particular, he was one of the key players in establishing human neuroimaging in Oxford. Here, we celebrate the role that he played in this endeavour, both in the early days of pulling together funding, and solving practical challenges, and in the following years, when we all appreciated his ongoing encouragement and support.